2016
DOI: 10.1080/10790268.2016.1226005
|View full text |Cite
|
Sign up to set email alerts
|

Transverse myelitis-like presentation of methanol intoxication: A case report and review of the literature

Abstract: We recommend performing MRI of the cervicothoracic spine in every methanol intoxication case to exclude both asymptomatic and symptomatic cases of spinal cord involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Methanol is well absorbed in the gastrointestinal tract, with peak levels reached within 30-90 minutes, and a serum half-life ranging from 14-20 hours (Brent et al, 2001). The volume of methanol distribution is 0.6-0.7 liters per kg, and it is primarily eliminated through liver metabolism, with only 2-5% excreted through the kidneys (Algahtani et al, 2018). Toxicity arises from the formation of formaldehyde and formic acid through liver alcohol dehydrogenase (Pereska et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methanol is well absorbed in the gastrointestinal tract, with peak levels reached within 30-90 minutes, and a serum half-life ranging from 14-20 hours (Brent et al, 2001). The volume of methanol distribution is 0.6-0.7 liters per kg, and it is primarily eliminated through liver metabolism, with only 2-5% excreted through the kidneys (Algahtani et al, 2018). Toxicity arises from the formation of formaldehyde and formic acid through liver alcohol dehydrogenase (Pereska et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the second re-treatment, the patient presented to the emergency room with a loss of consciousness accompanied by respiratory arrest. Respiratory arrest often serves as a terminal symptom occurring 6-36 hours after intoxication (Algahtani et al, 2018), indicating the possibility of the patient having an intoxication duration of ≥6 hours. Cardiopulmonary resuscitation (CPR) was performed following the American Heart Association Guideline (Drennan et al, 2020) In this condition, gastric lavage was not performed as the initial focus was on respiratory resuscitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of methanol mass poisoning in Estonia, Norway and Czechia have reported acute mortality of 18%-21%, whereas the rate of sequelae after survival ranged between 10% and 34%[ 13 ]. As the most serious complication, cerebral hemorrhage is relatively rare with reported prevalence of 7%-19%[ 14 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A literature search of methanol toxicity cases in Saudi Arabia (SA) revealed only four cases ( Algahtani et al, 2018 ; Althwanay et al, 2020 ; Owolabi et al, 2020 ). However, Galvez-Ruiz et al described outcomes of optic disk cupping following methanol poisoning in a series of 50 cases presenting at two large hospitals in Riyadh between 2008 and 2014, possibly indicating a higher incidence of methanol toxicity than perceived ( Galvez-Ruiz et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%